Pemikiran Pendidikan Masa Bani Umayyah Damaskus (661-750 M) - Ramadhani, Randy Pratama; Dewi, Eva; Rahman, Luthfi Anshori (Journal of Practice Learning and Educational Development, 2026)
This study examines the development of Islamic educational thought during the Umayyad Dynasty in Damascus (661-750 CE). The Umayyad Dynasty represents a significant period in Islamic educational history, marked by territorial expansion, educational institution development, and knowledge diversification. The research employs a library study method with a historical-descriptive approach. Findings indicate that during the Umayyad period, there was a transformation in Islamic education systems including: (1) emergence of various educational institutions such as Kuttab, Halaqah in mosques, private palace education, and literary councils; (2) curriculum development encompassing religious sciences, Arabic language, literature, history, and general sciences; (3) implementation of varied teaching methods according to educational levels. Factors contributing to educational excellence during this period include political stability, caliphal support, territorial expansion, and economic growth supporting scholarly activities.